2020
DOI: 10.1016/j.envsoft.2020.104761
|View full text |Cite
|
Sign up to set email alerts
|

Distributed long-term hourly streamflow predictions using deep learning – A case study for State of Iowa

Abstract: • Developed Neural Runoff Model (NRM) using deep learning for 120 hours streamflow forecasts. • NRM on 125 USGS stations in Iowa outperforms other machine learning methods. • NRM shows effectiveness in integrating stage level data for runoff forecasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(32 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…Kratzert et al [184] performed a study using Long Short Term Memory (LSTM) ANN over 241 catchments and showed the ability of this DL approach to learn long-term dependencies between the inputs and the output of the model (e.g., those related to modelling storage effects) along with the possibility to transfer process understanding from the regional to the local scale. Recently, Xiang and Demir [185] proposed the use of DL for extending the forecast horizon until five days on an hourly basis with promising results. Because there is a very recent interest on the application of DL for discharge forecasting, it has been tested by using only spatially distributed rainfall derived from dense rain gauges.…”
Section: Flash Flood Modelling Approaches Using Radar Datamentioning
confidence: 99%
“…Kratzert et al [184] performed a study using Long Short Term Memory (LSTM) ANN over 241 catchments and showed the ability of this DL approach to learn long-term dependencies between the inputs and the output of the model (e.g., those related to modelling storage effects) along with the possibility to transfer process understanding from the regional to the local scale. Recently, Xiang and Demir [185] proposed the use of DL for extending the forecast horizon until five days on an hourly basis with promising results. Because there is a very recent interest on the application of DL for discharge forecasting, it has been tested by using only spatially distributed rainfall derived from dense rain gauges.…”
Section: Flash Flood Modelling Approaches Using Radar Datamentioning
confidence: 99%
“…Due to the lack of systematic and standardized data collection on disasters, long-term planning becomes a critical challenge for decision-makers [39]. The standardized data and information [40] is a critical need for improving hydrological data management [41], remote sensing and monitoring [42], data analytics [43], and forecast and modeling studies [44][45][46]. Information generated through optimized data structures can support informed decision for flood management and control [47], preparedness [48], prevention [49], recovery, and response to future flood events and can be utilized for these applications.…”
Section: Flood Inventory Specificationmentioning
confidence: 99%
“…Water resource management and hydrological modeling using physically based or data-driven (i.e. artificial neural networks) approaches [15][16][17] need high-resolution DEM for accurate hydrological predictions [18]. Besides advanced hydrological modeling, monitoring and geographic analysis such as watershed delineation [19,20] and stage height measurements [21] benefit from DEMs.…”
Section: Introductionmentioning
confidence: 99%